Readiness of Medical Recording and Health Information Education Institutions in the Digital Transformation Era of UTAUT Based: Kesiapan Institusi Pendidikan Perekam Medis dan Informasi Kesehatan Era Transformasi Digital Berbasis UTAUT - Wilda Faida, Eka; Angesti, Dyan (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
Based on the results of the 2022 PERSI survey, Electronic Medical Records (EMR) ownership is not yet optimal. Permenkes Number 24 of 2022 concerning Medical Records, one of which mandates that EMR be mandatory in all hospitals in Indonesia. The Ministry of Health has a target in December 2023 to have completed the integration of One Health in all hospitals in Indonesia. Hospitals throughout Indonesia must race in the development of EMR according to the target of the Indonesian Ministry of Health. The aim to assist government programs by increasing knowledge of medical records and health information officers (PMIK) regarding the challenges and strategies of health education institutions in preparing graduates in the era of digital transformation of UTAUT-based health information. The method used is through an online national seminar with several speakers and attended by ≥ 570 participants. The results are achievement of increasing the enthusiasm of participants in increasing their knowledge with indicators of success obtaining post-test scores that are dominated by correct answers, interactive question, and answer discussions. The conclusion seminar activity can help government programs in increasing digital acceleration in Health Facilities, this can be continued in further research programs on evaluating the use of EMR.